Lateran IV theology and care of souls - Monagle, Clare 1973-; Şenocak, Neslihan 1976- (Brepols, 2022)
The Fourth Lateran Council of 1215 was a foundational event in the history of Western Christendom. Lead by the reformist Pope Innocent III, the Council ushered in a new era of papal policy in governance, the implications of which would be felt throughout the continent. To some, Lateran IV represents the flourishing of the medieval papacy, as the institution sought to improve pastoral care across Europe, as well as to define theological orthodoxy. For others, Lateran IV constitutes the founding moment of the so-called ‘persecuting society’, the moment at which the Papacy articulated its identity via the category of heresy. Lateran IV: Theology and Care of Souls assesses the pastoral and theological legacies of the Council. The volume brings together scholars of high theology, as well as those whose work engages with the practices of clerical governance in the thirteenth century. Lateran IV: Theology and Care of Souls maps the key intellectual, theological, and pastoral concerns of Lateran IV, especially revealing the influence of the medieval theologians connected to the universities on the decrees of the Council.
Keywords: Laterankonzil -- 4. -- 1215 -- Rom; Catholic Church / Doctrines / History; Lateran Council / (4th / 1215 / Palazzo Lateranense); Church history / Middle Ages, 600-1500; Aufsatzsammlung